Uji Efektivitas Antihiperglikemia Kombinasi Jus Pare (Momordica charantia L) dan Jus Tomat (Solanum lycopersicum L) pada Tikus Wistar Jantan dengan Metode Toleransi Glukosa - Wulandari (Universitas Indonesia, 2016)
Diabetes melitus (DM) is a metabolic disorder condition characterized by hyperglycemia. Bitter melon (Momordica charantia L) and tomato (Solanum lycopersicum L) are plant that have actvity antihiperglicemic actvity that contain triterpenoid, flavonoid, alkaloid, and saponin. The purpose of this study was to determine the effect of the combination antihiperglicemic bitter melon juice and tomato juice on male Wistar rats that was induced sucrose. Animals were divided into 6 groups. Blood glucose levels was measured at 30th, 60th, 90th and 120th minutes with enzymatic method using a glucometer. Data were analyzed statistically by Kruskal-Wallis and Mann-Whitney with a 95% confidence level. The research showed a blood glucose level of negative group differ significantly from the other group (P>0.05 ) and did not differ significantly with group 6 (P>0.05). Group 5 (bitter melon juice 17.4 g/KgBW and tomato juice 16.8 g/KgBW) has a significant difference (P<0.05) with other groups and more effectively lowering blood glucose levels from minute 90th to minute 120th. Group 5 has the lowering effect of blood glucose levels than single juice.